THREE NEW MALESIAN SPECIES OF GRAMINEAE - SOEJATMI DRANSFIELD (Reinwardtia, 1980)
Illustrated descriptions of three new Malesian species (Racemobambos ceramica S. Dransfield, Nastus schmutzii S. Dransfield and Cymbopogon minutiflorus S. Dransfield) are presented.R. ceramica is compared with R. schultzei (Pilger) Holttum, and N.schmutzii with N. reholttumianus S. Soenarko. N. reholttumianus, so far found only in the island of Sumba,is recorded also as occurring in Flores. C. minutiflorus is the first representative of the genus in Sulawesi.